Workshop Teknik Menganalisis Butir Soal dalam Meningkatkan Kompetensi Guru di SMK Cileungsi Bogor - Sumiati, Ati; Widiastuti, Umi; Suhud, Usep (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
Activities of devotion to the public were all intended to help the level of a unit of education and in the teacher raising the standard of living incompetence is the need of evaluation hands-on learning uses the technique that analysis an easy one and pleasing. Universitas Negeri Jakarta, as educators who took on the task of Tri Dharma Perguruan Tinggi. One of which is the third Darma, devotion to the public. The Implemented of it, educators and Faculty of Economics’ family member UNJ have done education for the public through the development of competence to Vocational High School’s teacher. Workshop technique analyzes details of the problem within increase competence of vocational teacher in evaluation learning accordance 2013 curriculum in VHS Cileungsi, Bogor, be held on Saturday, May 13th, 2197 in multi-function room VHS Amal Mulia Kab. Bogor that attend by all of the teachers. The workshop helps teachers in the evaluation of a test that used. The training is expected that could add more teacher’s knowledge about technique analyze details of the problem either qualitative or quantitative and could design question accordance with the achievement of competence effectively. In future, be expected will be model of technique analyze details of the problem for teacher either manual or electronic.